Taraf Layanan Konseling Islam Individu Siswa (Studi Kedisiplinan Di MA Ali Maksum Yogyakarta) - Isna Izayati (JURNAL INDO-ISLAMIKA, 2014)
There is student indiscipline in the disciplinary rules of MA Ali Maksum Yogyakarta. The indiscipline behavior carried out by MA Ali Maksum Yogyakarta students is the absence of students from an anonymous madrasah, often leaving late for the madrasah and not doing their assignments. This individual counseling is given to students who violate the discipline by the BK teacher by prioritizing the students so that nothing is meant. This study aims to see the stages of the implementation of individual counseling services in improving the discipline of students who are disciplined at MA Ali Maksum Yogyakarta. This research is a field research with a qualitative approach. The subjects of this study were counseling teachers and five students taken from class X IPA A, X IPS A, X Religion A. Methods of data using observation, interviews and documentation. The data analysis used in this research is descriptive qualitative.